HISTORIA DE LAS ENCUESTAS EN EL MUNDO - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
Abstract. Surveys: A general panorama: It knows what is the surveys, which are their main tools, what types of survey exist at present, how the group of people determines itself survey and which are the advantages and disadvantages of the survey. Definition of Survey: The survey is a method of the social investigation that consists of obtaining data of the people survey by means of the questionnaire use designed in previous form.